The influence of Zinc-Dialkyl-Dithiophosphate (ZDDP) additives on the tribological performance of RBD palm kernel / Nurul Farhanah Azman...[et al.] - Azman,, Nurul Farhanah; Samion, Syahrullail; Abd Rahim, Erween; Shunpei, Kamitani (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Vegetable oil based lubricant has received much attention in recent years due to its biodegradable properties, low toxicity and environmental friendly. This study used refined, bleached and deodorized (RBD) palm kernel blended with zinc-dialkyl-dithiophosphate (ZDDP) to evaluate the tribological performance as a potential alternative lubricant. The ZDDP additives were added with concentration of 0wt%, 1wt%, 3wt% and 5wt%. Commercial mineral oil SAE 40 was used for comparison purposes. The tests were performed at 1.5 m/s and 3.5 m/s of sliding speed under 9.81 applied load for 1 hour at room temperature. The results indicate that the presence of ZDDP in RBD palm kernel have improved both friction reducing and anti-wear performance. The formulation of RBD palm kernel have the potential to be used as a substitution for mineral based lubricant in near future. The authors would like to express their thanks to the Research Management Centre (RMC) of Universiti Teknologi Malaysia for the Research University Grant, GUP (12H98, 09H64), Fundamental Research Grant Scheme, FRGS (4F610), and Ministry of Education of Malaysia and Ministry of Higher Education for their support; they also thank the Faculty of Mechanical Engineering, Universiti Teknologi Malaysia for the laboratory facilities.